Recent Progress in Luminescent Cu(I) Halide Complexes: A Mini-Review - Mensah, Abraham; Shao, Juan-Juan; Ni, Jian-Ling; Li, Guang-Jun; Wang, Fang-Ming; Chen, Li-Zhuang (Frontiers in Chemistry, 2022)
Copper(I) halide complexes are well sought-after materials due to their rich structural diversities and photophysical properties. Profoundly, there is a direct relationship between each structural variation and luminescence of these complexes, for a purported use. In this review, recent publications within the last two years about copper(I) halide complexes, centering on their structural dimensionalities with derivatives of nitrogen, phosphorus, and sulfur ligands have been considered alongside their effects on luminescence.